If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12=-2(x-7+3x
We move all terms to the left:
12-(-2(x-7+3x)=0
We add all the numbers together, and all the variables
-(-2(4x-7)+12=0
| x−5=5(2x+3)−11 | | -6p+3+p=8 | | Y=22-2(5y) | | 4(2x)−3=18x+8 | | -24=-4r+8r | | -9=6x-5-2x+12 | | 0.5x=1+0.5x-2 | | 6x=4x+88 | | 0.5x=1+0.5x+2 | | 8x+4(x+4)=28 | | 1/2(2/3)^x=1/4(16/27) | | 2x+12=5x+27 | | -9=a-2-2 | | 3p+15=4+4p | | 2(3x1)=20 | | 2m+12=5m-18 | | r=54-33 | | 8=4v-7-7v | | -5a=14a | | 3b+15=7b-13 | | 4r-3r=-2 | | 90+X+20+2x-20=180 | | x/3+x/5=9 | | x^2-3=20 | | 18x-11=24+11x | | x2-3x-39=0 | | y=87-48 | | 8x+5=41-4x | | 2x=4x=6x | | 13+x^2=80 | | 6+x^2=9 | | 10d=3 |